Short-term cyproheptadine therapy in underweight children: Effects on growth and serum insulin-like growth factor-I - Pat Mahachoklertwattana (2018)
Background: Cyproheptadine, an appetite stimulant, has been used in poor-appetite underweight children. Its beneficial effects on enhancing growth rate have been demonstrated. In contrast, an adverse effect on blunting growth hormone (GH) secretion has also been reported. To date, however, its effect on insulin-like growth factor-I (IGF-I), a GH-mediated growth factor, has not been documented. Aim: To examine the effect of cyproheptadine therapy on growth and serum IGF-I in underweight children. Methods: Twenty-one underweight, otherwise healthy children were recruited. They were randomly assigned into cyproheptadine administration (n = 10) and placebo (n = 11) groups. The former received cyproheptadine for 4 months. Serum IGF-I levels were measured in both groups. Results: Weight and height velocities and IGF-I z-scores during cyproheptadine therapy were significantly greater in the intervention group than those of the placebo group. Conclusion: Cyproheptadine therapy in underweight children increased caloric intake and serum IGF-I concentration and consequently enhanced growth velocity. © Freund Publishing House Ltd.